Studi Biologi Ulat Bulu Lymantria marginata Wlk. (Lepidoptera : Lymantridae) Pada Tanaman Mangga - NI NENGAH DARMIATI; WAYAN SUSILA; NI KADEK NITA KARLINA ASTRIYANI ASTRIYANI (Fakultas Pertanian Universitas Udayana, 2012)
The study was conducted at the Laboratory of Plant Pest and Disease Management, Departmentof Agroecotechnology, Faculty of Agriculture, University of Udayana. The purpose of this study was todetermine the life cycle of caterpillars L. marginata, praoviposisi period, oviposition, pascaoviposisi,male imago long life, female imago long life and fecundity of caterpillars L. marginata and sex ratio ofcaterpillars L. marginataThe results showed that the life cycle of L. marginata average of 52.00 ± 3.68 days with an eggstage was 8.20 ± 1.88 days, larval stage average 29.05 ± 1.76 days, and the pupal stage an average of12.60 ± 2.18 days (n = 20).The number of eggs laid by the female imago is 2872 grains with an average 143.60 ± 34.63 eggsper imago, with praoviposisi period was 2.15 ± 0.75 days, oviposition period of 1.80 ± 0.77 days, aperiod pascaoviposisi 2.05 ± 0.83 days. Females imago long live ranged from 5-7 days with an averageof 6 ± 0.85 days and males imago long life ranged from 2-7 days with an average of 4.5 ± 1.54 days(n = 20). Sex ratio of L. marginata approaching 1:1 (47% males and 53% females